Aeolian creeping mass of different grain sizes over sand beds of varying length. Issue 7 (27th July 2015) - Cheng, Hong; Liu, Chenchen; Zou, Xueyong; Li, Jifeng; He, Jiajia; Liu, Bo; Wu, Yongqiu; Kang, Liqiang; Fang, Yi
Abstract Creep is an important mode of aeolian sand transport, but it has received little attention in previous studies due to experimental difficulties and insufficient theory. In this study, we conducted 116 groups of experiments with three repeats for each group in a wind tunnel to measure the creeping mass of four different mean grain sizes (152, 257, 321, and 382 µm) over six bed lengths (2.0, 3.5, 5.0, 6.5, 8.0, and 10.0 m) at six different friction velocities (0.23, 0.35, 0.41, 0.47, 0.55, and 0.61 m/s). We attempted to develop a comprehensive model of the aeolian creeping mass by analyzing the effect of wind velocity, the particle size, and the sand bed length based on the experimental data. The primary conclusions are as follows: (1) the complex relationship among the wind velocity, the grain size, the length of the bed, and the surface shape determines sand creep. There was no unified formula to express the effect of particle sizes and the sand bed length on aeolian creeping masses, and their effects appeared to depend on each other and wind velocity, whereas the creeping mass increases with increasing wind velocity for any particle size with any length of sand bed. (2) This paper presented a predicting model to determine the aeolian creeping mass, whose calculating results can match to experimental data with correlation coefficients (R2) of 0.94 or higher. (3) The effect of grain size on creeping mass can be classified into three categories: the creeping mass increases with increasing grain size, the creeping mass initially decreases and subsequently increases with increasing grain size, and the creeping mass fluctuates with the grain size. (4) The effect of increasing bed length appears to depend on the grain size. For mean grain sizes of 152, 257, and 321 µm, creep initially increases with increasing bed length before decreasing above a certain value, while for a mean grain size of 382 µm, the creeping mass gradually increased with increasing bed length. The results help to elucidate aeolian creep and provide an intense foundation for advanced study.